Consumer Expenditure Survey, 1992: Diary Survey ([Verlag nicht ermittelbar], 1995)
The ongoing Consumer Expenditure Survey (CES) provides a continuous flow of information on the buying habits of American consumers and also furnishes data to support periodic revisions of the Consumer Price Index. The survey consists of two separate components: (1) a quarterly Interview Survey in which each consumer unit in the sample is interviewed every three months over a 15-month period, and (2) a Diary Survey completed by the sample consumer units for two consecutive one-week periods. The Diary Survey contains consumer information on small, frequently purchased items such as food, beverages, food consumed away from home, gasoline, housekeeping supplies, nonprescription drugs and medical supplies, and personal care products and services. Participants were asked to maintain expense records, or diaries, of all purchases made each day for two consecutive one-week periods. Information was also elicited at the end of the two-week period on work experience, occupation, industry, retirement status, earnings from wages and salaries, net income from business or profession, net income from one's own farm, and income from other sources. The Consumer Unit Characteristics and Income (FMLY) files supply information on consumer unit characteristics, consumer unit income, and characteristics and earnings of the reference person and his or her spouse. A consumer unit consists of all members of a particular housing unit who are related by blood, marriage, adoption, or some other legal arrangement. Consumer unit determination for unrelated persons is based on financial independence. Member Characteristics (MEMB) files contain selected characteristics for each consumer unit member, including reference person and spouse. The Detailed Expenditures (EXPN) files present weekly data on expenditures at the Universal Classification Code (UCC) level, while the Income (DTAB) files contain weekly data on income at the UCC level. An additional file, Part 20, includes sample programs that can be used for various types of data extraction.